PENGGUNAAN MATERIAL 316L UNTUK GREEN-PART TEST PIECE DENGAN TEKNIK METAL INJECTION MOLDING - Muhammad Nauval Fauzi; Haruman Wiranegara (Jurnal Rekayasa Mesin, 2023)
Material 316L is one type of iron with excellence corrosion resistant and was used in many industries. 316L is used as feed stock material for Green-part test piece which is a product of the Metal Injection Molding (MIM) process. The study showed, the manufacture of green part made from standard 316L material has been carried out. Green part is a product made by injection mold stage from MIM process. The stages of research carried out refer to the Metal Injection Molding process with the standard references that included three stages carried out which are the preparation of feedstock, mold design, and mold testing with the injection process by testing material and by the 316L feedstock. The purpose of this study is to analyze the  green part test piece that was made with 316L material in MIM process with a specific measurement and the quality of the end product using tensile test.  Results of this study indicate that the right parameters was achieved to produce shapes that match the targeted geometry of the 316L feed stock material. The  tensile strength test show reading of 110Mpa but when compared with other studies, the value was still under standard.